2015
DOI: 10.2174/1570159x13999150210141444
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology of Ultrasonic Vocalizations in adult Rats: Significance, Call Classification and Neural Substrate

Abstract: Pharmacological studies of emotional arousal and initiation of emotional states in rats measured by their ultrasonic vocalizations are reviewed. It is postulated that emission of vocalizations is an inseparable feature of emotional states and it evolved from mother-infant interaction. Positive emotional states are associated with emission of 50 kHz vocalizations that could be induced by rewarding situations and dopaminergic activation of the nucleus accumbens and are mediated by D1, D2, and partially D3 dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
101
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 153 publications
(217 reference statements)
8
101
0
Order By: Relevance
“…We observed that suvorexant attenuated 50-kHz USVs during each of pre- and post-lever time-points. Our prior work shows that suvorexant pretreatment suppresses cocaine-evoked elevations in ventral striatal dopamine (Gentile et al 2017) which supports the hypothesis that mesolimbic dopamine underlies the elicitation of 50-kHz USVs (for reviews, see Barker et al 2015; Brudzynski 2015). From the three categories of call types analyzed in the present report, 50-kHz USV call type remained stable irrespective of suvorexant pre-treatment with majority of calls belonging to FM 1–2 call type which supports earlier work describing USVs associated with cocaine-paired cue presentation (Meyer et al 2012).…”
Section: Discussionsupporting
confidence: 77%
“…We observed that suvorexant attenuated 50-kHz USVs during each of pre- and post-lever time-points. Our prior work shows that suvorexant pretreatment suppresses cocaine-evoked elevations in ventral striatal dopamine (Gentile et al 2017) which supports the hypothesis that mesolimbic dopamine underlies the elicitation of 50-kHz USVs (for reviews, see Barker et al 2015; Brudzynski 2015). From the three categories of call types analyzed in the present report, 50-kHz USV call type remained stable irrespective of suvorexant pre-treatment with majority of calls belonging to FM 1–2 call type which supports earlier work describing USVs associated with cocaine-paired cue presentation (Meyer et al 2012).…”
Section: Discussionsupporting
confidence: 77%
“…DA has been strongly associated with reward processing 111,112 and 50-kHz ultrasonic communication. 113,114 Importantly, DA signaling is profoundly altered in mice with genetic modifications targeting Cacna1c, 115 with evidence for sex-dependency of Cacna1c depletion effects. 12 This is in line with previous findings reporting a lack of repetitive and stereotyped patterns of behavior in Cacna1c +/− mice, as assessed by means of self-grooming 129 and marble-burying.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, however, it was reported that Ca v 1.2 is a target of estradiol in vivo and that estradiol directly potentiates Ca 2+ influx via Ca v 1.2 through the dihydropyridine binding site 109. DA has been strongly associated with reward processing 111,112 and 50-kHz ultrasonic communication 113,114. Another potential candidate appears to be the neurotransmitter dopamine (DA).…”
mentioning
confidence: 99%
“…On the other hand, it has been also well described that laboratory rats (Rattus norvegicus domesticus) produce USV syllables which have two predominant categories: one has a relatively higher frequency (around 50 kHz) with a few ten milliseconds in duration, and the other is in the low frequency range (~22 kHz) but much longer duration. These two USV syllables are here named as 'pleasant' and 'distress' syllables since these are generally considered to be indicators of positive and negative emotional states, respectively [6][7][8][9]. This categorization appears to be preserved in different strains of rats, though a slight difference in duration has been reported (Sales, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Perception of these call also have suggested an effect to modulate listeners' affective states [20]. Further discrimination of subcategories in the pleasant call has been studied to better know their functional difference in different situations [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%